Hubungan Self-Regulated Learning dengan Goal Orientation pada Mahasiswa Universitas X di Masa Pandemi - Oktaffiana Oktaffiana; Budi Sulaeman (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
This study aims to see the correlation between self-regulated learning and goal orientation among students of the humanities faculty of University X in the pandemic era. The study used correlational quantitative methods with 70 participants who were given two measuring scales in the form of a google form questionnaire. The first measuring scale uses a scale compiled by Budi Sulaeman as a BINUS Psychology lecturer based on the self- regulation cycle proposed by Zimmerman (in Susetyo & Kumara, 2012) to measure self-regulated learning and a measuring scale modified by Rono J (2012) based on goal orientation theory. to measure goal orientation. Using pearson correlation analysis, show that self-regulated learning has a positive and significantly correlation with goal orientation (r = 0.730, p < .001), so Ha is accepted and H0 is rejected.